Driving economic success: Fintech, tourism, FDI, and digitalization in the top 10 tourist destinations - Xu, Anfeng; Siddik, Abu Bakkar; Sobhani, Farid Ahammad; Rahman, Md. Mominur (Humanities & social sciences communications, 2024)
Economic growth in leading tourist destinations faces challenges requiring investment, technological advancement, and resource management. This study examines the impact of tourism, Fintech, FDI, and digitalization on economic growth in Austria, France, Germany, Greece, Italy, Mexico, Spain, Turkey, the UK, and the USA. These countries, identified by UNWTO for 2022, represent 46% of the global tourism market. Utilizing yearly data from 2010 to 2022 from sources like the World Bank, Crunchbase, and UNWTO, we apply Pooled OLS, PCSEs, FGLS, and Two-Step GMM models using Stata v17.0. Additionally, Necessary Condition Analysis (NCA) was conducted using SmartPLS v.4.3 software. Our findings reveal that Fintech, tourism, FDI, and digitalization significantly contribute to economic growth, with varying degrees of impact across different models. Specifically, digitalization and tourism demonstrate the most substantial positive effects, while FDI and Fintech also play crucial roles. The study highlights the necessity of integrating these factors to foster sustainable economic growth in top tourist destinations. These results provide actionable insights for policymakers, stakeholders, and government officials, emphasizing the importance of strategic investments in Fintech, tourism, FDI, and digital infrastructure to enhance economic performance. The implications of this research extend to informing policy formulation and strategic decision-making aimed at leveraging technological advancements and investments for sustained economic development in major tourist economies.